2008
DOI: 10.1038/bjp.2008.108
|View full text |Cite
|
Sign up to set email alerts
|

The expression and function of Ca2+‐sensing receptors in rat mesenteric artery; comparative studies using a model of type II diabetes

Abstract: Background and purpose: The extracellular calcium-sensing receptor (CaR) in vascular endothelial cells activates endothelial intermediate-conductance, calcium-sensitive K þ channels (IK Ca ) indirectly leading to myocyte hyperpolarization. We determined whether CaR expression and function was modified in a rat model of type II diabetes. Experimental approach: Pressure myography, western blotting, sharp microelectrode and K þ -selective electrode recordings were used to investigate the functional expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 37 publications
5
68
1
Order By: Relevance
“…A comprehensive analysis of factors involved in the relaxation revealed that this was associated with suppressed EDH-like response and accordingly a reduction in IK Ca channel expression. Interestingly, endothelial dysfunction in Type 2 diabetic rats is also associated with reduced IK Ca expression (10,69), and this expressional change was, at least in part, due to elevated oxidative stress of endothelial cells (72). Whether increased oxidative stress in depression-like state (5,39,45,48) can affect IK Ca is not known.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive analysis of factors involved in the relaxation revealed that this was associated with suppressed EDH-like response and accordingly a reduction in IK Ca channel expression. Interestingly, endothelial dysfunction in Type 2 diabetic rats is also associated with reduced IK Ca expression (10,69), and this expressional change was, at least in part, due to elevated oxidative stress of endothelial cells (72). Whether increased oxidative stress in depression-like state (5,39,45,48) can affect IK Ca is not known.…”
Section: Discussionmentioning
confidence: 99%
“…47 On the endothelium, the link between activation of the CaSR and KCa3.1-channels is disrupted in mesenteric arteries from a model of type II diabetes, possibly reflecting decreased expression of CaSRs, although KCa3.1-channel protein, but not hyperpolarization, was also reduced. 48 The CaSR and KCa3.1-channel are colocalized in caveolin-poor regions of the EC membrane in those arteries. 45 KCa2.3-channels localize within the caveolae so abundant in ECs and, inter alia, act as signaling platforms.…”
Section: Endothelium-dependent Hyperpolarizationmentioning
confidence: 95%
“…g) K + -selective microelectrode recording from the extracellular space between myocytes in an intact rat mesenteric artery; the thromboxane A 2 receptor agonist U46619 elevated [K + ] o , an effect reversed by iberiotoxin. Data adapted from [19,40,45,112,135,138]; see text for further details subsequent myocyte hyperpolarisation. Instead, endothelial cell hyperpolarisation might simply be conducted via low resistance, gap junctional pathways to the myocyte (see [29,30,63]).…”
Section: Ik Ca Characteristicsmentioning
confidence: 99%